Locker Hero - Russell, Rachel Renee; Russell, Erin; Russell, Nikki (New York Aladdin, 2016)
Questioning his resolve to attend public school after being home schooled when he is targeted by a bully, Max aspires to become like his favorite comic book heroes and finds an unexpected opportunity to be the hero his middle school needs.
660L
103858
Keywords: Bullies; Cartoons and comics; Middle schools; Schools